General geology and karst geomorphology of Padang Kuala Semor, Gua Musang Kelantan - Muhamad Izhar Abu Bakar (2017)
Geological and Geomorphologic Mapping-based methodology has been used in the process of identifying karsts formation/landform. The study area was located at Padang Kuala Semor, Gua Musang, Kelantan. The main purposes of this study are to update geological map of the study area, to identify karst formation/landform and to produce karst geomorphologic map of Padang Kuala Semor. The geological mapping was conducted at the study area to determine the geology and followed by making a conclusion about formation of the area. The study area is included t the Gua Musang formation based on the type of rock that has been identified at Padang Kuala Semor, surface karst, subsurface karst and surficial landform. Geomorphologic mapping was successfully done with the help of interpretation from Google Earth in order to identify karst formation/landform.